2015
DOI: 10.1590/01000683rbcs20140358
|View full text |Cite
|
Sign up to set email alerts
|

Pedo-Transfer Functions for Estimating Soil Bulk Density in Central Amazonia

Abstract: Under field conditions in the Amazon forest, soil bulk density is difficult to measure. Rigorous methodological criteria must be applied to obtain reliable inventories of C stocks and soil nutrients, making this process expensive and sometimes unfeasible. This study aimed to generate models to estimate soil bulk density based on parameters that can be easily and reliably measured in the field and that are available in many soil-related inventories. Stepwise regression models to predict bulk density were develo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
2
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 23 publications
(23 reference statements)
1
7
2
3
Order By: Relevance
“…The Bernoux et al (1998) model presented the highest RMSPE value and our model the lowest (Table 5). Barros and Fearnside (2015) also developed PTFs for Oxisols in the Central Amazon region and compared the performance of their model with those presented by authors reported in this work (Benites et al, 2007;Bernoux et al, 1998;Tomasella and Hodnett, 1998). The authors found that the application of these three PTFs overestimate soil bulk density, which is in agreement with our findings.…”
Section: +3supporting
confidence: 90%
See 3 more Smart Citations
“…The Bernoux et al (1998) model presented the highest RMSPE value and our model the lowest (Table 5). Barros and Fearnside (2015) also developed PTFs for Oxisols in the Central Amazon region and compared the performance of their model with those presented by authors reported in this work (Benites et al, 2007;Bernoux et al, 1998;Tomasella and Hodnett, 1998). The authors found that the application of these three PTFs overestimate soil bulk density, which is in agreement with our findings.…”
Section: +3supporting
confidence: 90%
“…The authors found that the application of these three PTFs overestimate soil bulk density, which is in agreement with our findings. However, we highlight that the soil bulk density determined by Barros and Fearnside (2015) is significantly lower than what we found in the region of the Urucu River (average and median values of 0.66 and 0.62, respectively). This can explain why even the model developed by Tomasella and Hodnett (1998) also overestimated soil bulk density in the Oxisols evaluated by Barros and Fearnside (2015).…”
Section: +3contrasting
confidence: 79%
See 2 more Smart Citations
“…In general, the soils are highly weathered, deep, clayey, and porous [51,52]. Using mean texture values from the literature [52][53][54][55][56][57][58], the main soil parameters such as bulk density, available water capacity, and saturated hydraulic conductivity were estimated using pedotransfer functions developed for Amazonian soils [51,[59][60][61][62].…”
mentioning
confidence: 99%